Evaluation of the MD Anderson tumor score for diffuse large B‐cell lymphoma in the rituximab era. (18th February 2020) - Gutierrez, Antonio; Bento, Leyre; Diaz‐Lopez, Antonio; Barranco, Gilberto; Garcia‐Recio, Marta; Lopez‐Guillermo, Armando; Dlouhy, Ivan; Rovira, Jordina; Rodriguez, Mario; Sanchez Pina, Jose María; Baile, Monica; Martín, Alejandro; et al.
Abstract: Objectives: Diffuse large B‐cell lymphoma (DLBCL) is an aggressive heterogeneous lymphoma with standard treatment. However, 30%‐40% of patients still fail, so we should know which patients are candidates for alternative therapies. IPI is the main prognostic score but, in the rituximab era, it cannot identify a very high‐risk (HR) subset. The MD Anderson Cancer Center reported a score in the prerituximab era exclusively considering tumor‐related variables: Tumor Score (TS). We aim to validate TS in the rituximab era and to analyze its current potential role. Methods: From GELTAMO DLBCL registry, we selected those patients homogeneously treated with R‐CHOP (n = 1327). Results: Five‐years PFS and OS were 62% and 74%. All variables retained an independent prognostic role in the revised TS (R‐TS), identifying four different risk groups, with 5‐years PFS of 86%, 71%, 50%, and very HR (28%). With a further categorization of three variables of the original TS (Ann Arbor Stage, LDH and B2M), we generated a new index that allowed an improvement in HR assessment. Conclusions: (a) All variables of the original TS retain an independent prognostic role, and R‐TS remains predictive in the rituximab era; (b) R‐TS and additional categorization of LDH, B2M, and AA stage (enhanced TS) increased the ability to identify HR subsets.